The total extract of Abelmoschus manihot (L.) medic flowers (TEA) mediated Nrf2-TFAM signalling to regulate mitochondrial antioxidant mechanism - Ying Song; Xinyi Zhu; Beibei Wang; Qisong Li; Biwei Song (Scientific Reports)
Abstract Skin, as the first line of defence of the human body, is exposed to dangers such as overheating substances, ultraviolet rays, and environmental pollutants, and the incidence of skin diseases is increasing annually. Oxidative stress plays a dominant role in most skin diseases. Abelmoschus manihot (L.) medic flower (TEA) is a traditional Chinese medicine widely used to treat injuries to the skin such as water and fire scalds. It has been reported that TEA has excellent antioxidant effects. In this study, we aimed to explore the antioxidant and mitochondrial protection effects of TEA in H2O2-mediated HaCaT cell damage. HaCaT cells were incubated with H2O2 to simulate oxidative stress in the skin. The effect of TEA on HaCaT cells was also evaluated. Cell morphology was observed via inverted microscopy, and cell viability was measured via the MTT reagent. The cells were stained with Hoechst 33,324 solution. Reactive oxygen species (ROS), superoxide dismutase (SOD), malondialdehyde (MDA) and ATP detection kits were used to detect the corresponding indicators. The mitochondrial membrane potential was detected by JC-1. RT-PCR was used to detect mRNA and mtDNA expression. The expression of the target protein was detected by Western blotting and immunofluorescence. H2O2 triggered oxidative damage in HaCaT cells, which manifested as apoptosis, increased ROS and MDA contents, and decreased SOD activity. H2O2 activates the KEAP1/Nrf2/NQO1 signalling pathway, which decreases the expression of the intracellular KEAP1 protein and slightly increases the expression of the Nrf2 and NQO1 proteins, further causing mitochondrial oxidative stress, resulting in changes in the mitochondrial membrane potential, a reduction in the mtDNA copy number, and decreased expression of the PGC-1α and TFAM proteins. In addition the expression of mitochondrial respiratory chain genes and proteins decreased. TEA promoted the expression of Nrf2 in HaCaT cells, activated the downstream antioxidant response, and alleviated the oxidative stress and mitochondrial damage caused by H2O2. ML385 is an Nrf2 inhibitor, under which the antioxidant and mitochondrial protective effects of TEA are inhibited. When TFAM was knocked down, the protective effect of TEA on mitochondria was also inhibited. TEA protects HaCaT cells from H2O2-induced oxidative damage and mitochondrial oxidative damage through the KEAP1/Nrf2/NQO1/PGC-1α/TFAM pathway.